Znaczenie pracowników przedsiębiorstw projakościowych i ich wpływ na doskonalenie jakości wytwarzanych wyrobów - Chojnacka, Małgorzata (The Importance of Workers of Pro-Quality Enterprises and Their Influence on Improving the Quality of Goods Produced, 2008)
The result of the changes that take place in enterprises directed to the improvement of product quality is the increase in the importance of human resources. The goal of the report is to show how theory in this range is implemented in practice in modern organizations. The author presents results of the research carried out in four companies of the paper industry. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 31, s. 454-466